PENGEMBANGAN MEDIA SCRAPBOOK PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Widya, Widya; Putri Ami, Weni (LP2M Universitas Adzkia, 2024)
This study was motivated by the use of learning media that is still limited to printed textbooks and lacks the use of concrete media. The aim of this research is to develop a scrapbook learning media for Theme 2 “Always Save Energy”, Sub-theme 1